2016
DOI: 10.1002/2015jc010974
|View full text |Cite
|
Sign up to set email alerts
|

Lateral variability of sediment transport in the Delaware Estuary

Abstract: Lateral processes contribute significantly to circulation and material transport in estuaries. The mechanisms controlling transport may vary spatially such that shallow and deep regions of an estuary contribute differently to the total transport. An observational study was conducted to explore the importance of lateral variability in sediment transport mechanisms in the Delaware Estuary. Seven moorings were deployed across the channel in the region of the estuarine turbidity maximum (ETM) zone from April to Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 26 publications
2
47
0
1
Order By: Relevance
“…The suspended sediment concentration at the seaward boundary of the physical domain ( C m ) is prescribed to be a constant. The value of C m is determined by prescribing the averaged sediment availability a in the physical domain a=0Ltruey1y2a dydx0Ltruey1y2dydx to be constant, such that a maximum residual SSC of ∼200 mg L −1 representative for the observed ETM in the Delaware estuary under a relatively small river discharge (∼288 m 3·s −1 ; see McSweeney et al, ) is obtained.…”
Section: Default Experimentssupporting
confidence: 52%
See 2 more Smart Citations
“…The suspended sediment concentration at the seaward boundary of the physical domain ( C m ) is prescribed to be a constant. The value of C m is determined by prescribing the averaged sediment availability a in the physical domain a=0Ltruey1y2a dydx0Ltruey1y2dydx to be constant, such that a maximum residual SSC of ∼200 mg L −1 representative for the observed ETM in the Delaware estuary under a relatively small river discharge (∼288 m 3·s −1 ; see McSweeney et al, ) is obtained.…”
Section: Default Experimentssupporting
confidence: 52%
“…Nevertheless, since the SSC and a are strongly related (following equations and ), the reliability of a can be assessed by comparing the simulated SSC's to observations. It is found that the main features of the ETM in the Delaware estuary observed by McSweeney et al () are qualitatively reproduced. First of all, the ETM is centered around 100 km for the river discharge used here (288 m 3·s −1 ), with the region of elevated SSC distributed between approximately 80 km and 120 km from the mouth.…”
Section: Influence Of Coriolis Deflectionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is found that the stratification in the central region of salt intrusion increases with increasing river discharge, consistent with model studies (Ralston et al 2008;Lerczak et al 2009) andobservations (McSweeney et al 2016). The top-to-bottom salinity differences (less than 1.5 psu), however, are much smaller than the observed values during large river discharges (McSweeney et al 2016). This implies that the relatively strong stratification in case of large river discharges is not resolved in this model, which is probably the reason for the overestimated impact of river discharge on salt intrusion.…”
Section: Response To River Dischargementioning
confidence: 52%
“…YU et al, 2014 ;MCSWEENEY et al, 2016 ;JALON-ROJAS et al, 2016 ;TOUBLANC et al, 2016). De plus, la remise en suspension des sédiments sur les bancs à l'embouchure et les opérations de dragage le long des chenaux de navigation jouent un rôle très important (AVOINE et al, 1981 ;LE HIR et al, 2001 ;MARMIN et al, 2014).…”
Section: Introductionunclassified